Національні меншини Одеси наприкінці ХVIII - на початку XIX ст. - Шевчук - Бєла, Я.В.; Шевчук - Бела, Я.В.; Shevchuk - Bela, Ja (My University, 2011)
In the article talked about settling of south edge of the Russian empire by the different groups of population (Greeks, jewries, Armenians, Germans, Bulgarians, Poland), about the ways of their arrival in a region, about confes- sions belonging, economic state of colonies and policy of the Russian govern- ment, and also determination of concept "national minority".
Шевчук - Бєла Я.В.Національні меншини Одеси наприкінці ХVIII - на початку XIX ст. / Я.В. Шевчук - Бєла // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С.315 - 321.
Keywords: Меньшини; Національні меньшини; Меньшини Одеси; Меньшини Одеси XVIII - XIX ст.; Меньшинство; Национальное меньшинство; Меньшинство Одессы XVIII - XIXст.; Меньшинство Одессы; A minority of Odessa; A minority of Odessa XVIII - XIXst.; national minority; minority